Application of the reactivity method on KSU TRIGA fuel - Alshogeathri, Saqr Mofleh (Kansas State University, 2017)
The reactivity method is an indirect nondestructive technique to estimate integral burnup in fuel elements. In this method, the assumption is made that reactivity worth of a fuel element is a known function of burnup, often a linear relationship. When a fuel element burns, reactivity is reduced due to depletion of fissile actinides and generation of neutron-absorbing fission products. Currently, there is a lack of experimental data to verify the current composition of the KSU TRIGA (Training Research Isotopes General Atomics) fuel. Moreover, the KSU TRIGA Mark II staff method of estimating burnup is admittedly inaccurate due to its simple approximations. This work presents the positive period technique as convenient method use only the excess reactivity of the KSU core to compute reactivity via the inhour equation. Period measurements are determined via extraction and manipulation of the time dependent power data in the measurements. MCNP and Serpent modeling codes are both used extract the neutron kinetics parameters necessary in the inhour equation. Seven axial discretization of the KSU fuel was modeled, which minimizes the reactivity biases as function of burnup. Moreover, two unit cell models of the KSU TRIGA fuel were investigated. Modeled reactivity worths were computed using the KCODE in MCNP for comparative analysis. The burnup steps using two power peaking factor methods were developed to account for the biases introduced initial burnup of fuel prior to installation at KSU. By using the error distribution given by the two method to generate 200 test cases of the burnup steps can yield to reactivity worths as a function of burnup with quantifiable uncertainties. Finally, the results suggest that validation from another nondestructive technique such as gamma spectroscopy is necessary to asses the reactivity biases observed for higher burnup fuel elements due to unknown radial orientations. This work ultimately supports the production of a high-fidelity model of the KSU reactor.
Keywords: MCNP; Serpent; TRIGA; Fuel; Nondestructive; Burnup; LogbookReactivity